Implications of Storing Original Diplomas on The Security of Employee Documents in A Fixed – Time Work Agreement - Budiyana, Putu Eka; Sukadana, I Ketut; Ujianti, Ni Made Puspasutari (Sahabat Publikasi, 2024)
The company maintains original diplomas to prevent employees from leaving their jobs before completing their employment contracts and to build employee loyalty. The formulation of the research problem is, 1. What is the validity of keeping original diplomas by the company for employees in a Specific Time Work Agreement (PKWT)? 2. What are the implications of storing original diplomas for the security of employee documents in a Specific Time Work Agreement (PKWT)? The research method used is the normative legal research method. The research results show that storing original diplomas is said to be legal because the Employment Law does not explicitly regulate the prohibition on storing original diplomas or other documents belonging to employees, but an agreement arises in Article 1320 of the Civil Code in the form of a Specific Time Work Agreement (PKWT). between the company and employees. Storing original diplomas by the company for employees has implications for the security risks of the employee's documents, if the original diploma is lost, damaged or affected by a disaster, there will be no replacement or duplicate for the diploma in question.